“Enhancing equitable impact: ethical, legal, and sustainable approaches in short-term surgical outreach for global child health” - Blumenthal, Zoe; Farhat, Walid A.; McQueen, Kelly (Frontiers in Pediatrics, 2025)
Global health prioritizes improving health and achieving equity in health for all people worldwide. It encompasses a wide range of efforts, including disease prevention and treatment, health promotion, healthcare delivery, and addressing health disparities across borders. Short-term medical and surgical missions often contribute to the global health landscape, especially in low and lower-middle income countries. These programs aim to provide healthcare services to underserved populations and-often face challenges related to governance, ethical boundaries, and legal dimensions. Without adequate oversight and accountability, short-term medical and surgical missions may inadvertently perpetuate harmful practices, negatively impact the native healthcare system, and/or fail to address the long-term health needs of the communities they serve. The impact of short-term surgical trips has raised concerns regarding the need for capacity building initiatives, as well as the ethical and legal aspects of short-term medical and surgical missions. Short term surgical aid has a long history and has likely positively impacted the lives of children and adults with no other option for surgical, especially complex surgical care. These same short-term interventions have also been appropriately criticized for a lack of continuity of care, limited focus on training and education of local providers and capacity building within the local health systems, and perpetuation of power imbalances and neocolonialism. In response, there is an increasing call for a more comprehensive approach that incorporates capacity building and establish robust frameworks that ensure quality improvement, outcomes analysis, ethical conduct, sustainability, and equitable impact of short-term medical and surgical missions within global health. Child health is a critical concern, especially in less developed countries where almost half the population is under 20 years old. Pediatric surgical conditions have a significant impact on child health, and integrating surgical care with global health initiatives can effectively address important child health goals. Global surgery and global pediatric surgery aim to improve health outcomes and achieve equity in surgical care for underserved populations. Pediatric surgical conditions encompass various diseases, with a substantial portion requiring time-sensitive interventions. Establishing sustainable pediatric surgical capabilities within local health systems, including governance, alignment with health priorities, and effective leadership, is crucial. Selecting and supporting individuals for training and ensuring timely access to quality specialist advice are essential for achieving positive clinical outcomes. This review examines existing recommendations for ensuring the sustainable benefit of short-term medical missions, with a specific focus on surgical outreach trips. It highlights the need for standardization and emphasizes the importance of considering the legal and ethical dimensions in guiding these missions. Key aspects include the promotion of local leadership, cultural contextualization, and field-testing of guidelines. By incorporating these elements, medical missions can strive to achieve quality improvement, adhere to ethical principles, and operate within legal frameworks, thereby maximizing their impact and contributing to global health endeavors.